ChemInform Abstract: A Metal‐Free and Recyclable Synthesis of Benzothiazoles Using Thiourea as a Sulfur Surrogate. Issue 29 (July 2015) - Yin, Yan; Zhou, Hong; Liu, Xichen; Chen, Haiying; Wu, Fanhong; Zhang, Heng; Tao, Ruiheng; Cheng, Fengkai; Feng, Yangbo
Abstract Treatment of substrates (I) with thiourea and TFA gives benzothiazoles (IV) and TFA salts (V).